ANALISIS PARTISIPASI ANGGOTA KOPERASI KARYAWAN TIRTA DHARMA KHATULISTIWA KOTA PONTIANAK - Mulyati, Sri; Aminuyati, Aminuyati; Purwaningsih, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this study was to determine the participation of Tirta Dharma Khatulistiwa Employees Cooperative Members in Pontianak City ". The method used is descriptive method in the form of case studies with a sample of 75 respondents from 1435 populations. The technique used is direct communication techniques, indirect communication techniques and documentary study techniques. The research tools used in the form of interview guides, questionnaires and documents. The results of the research conducted showed that: 1) That the types of dominant member participation in the Employee Cooperative Tirta Dharma Equator Pontianak, namely: a. Pay mandatory contributions in an orderly and orderly manner b. Saving voluntarily so that it will be able to increase cooperative capital c. Utilizing cooperative services in the form of using goods or services provided by cooperatives d. Utilizing cooperative loan funds by observing installments e. Attend meetings and meetings actively. 2) Forms of member participation include: a) Member participation in participating in RATs, b) Member participation in investments and c) Member participation in utilizing services provided by cooperatives. The three forms of participation of cooperative members are very instrumental in determining the success of a cooperative business. 3) Factors causing the low participation of members of the Tirta Dharma Employee Cooperative Pontianak City, most of the members of the Pontianak City Tirta Dharma Employee Cooperative felt less satisfied with the services provided by the management at the savings and loan business unit.Â Keywords: Members, Participation, of Cooperative